Peptides derived from the integrin β cytoplasmic tails inhibit angiogenesis - Cao, Zhongyuan (Cell Commun Signal, 2018)
BACKGROUND: Integrins are essential regulators of angiogenesis. However, the antiangiogenic potential of peptides derived from the integrin cytoplasmic tails (CT) remains mostly undetermined. METHODS: Here we designed a panel of membrane-penetrating peptides (termed as mβCTPs), each comprising a C-terminal NxxY motif from one of the conserved integrin β CTs, and evaluated their antiangiogenic ability using both in vitro and in vivo approaches. RESULTS: We found that mβ3CTP, mβ5CTP and mβ6CTP, derived respectively from the integrin β3, β5 and β6 CTs, but not others, exhibit antiangiogenic ability. Interestingly, we observed that the integrin β3, β5 and β6 CTs but not others are able to interact with β(3)-endonexin. In addition, the antiangiogenic core in mβ3CTP is identical to a previously identified β(3)-endonexin binding region in the integrin β3 CT, indicating that the antiangiogenic mβCTPs may function via their binding to β(3)-endonexin. Consistently, knockdown of endogenous β(3)-endonexin in HUVECs significantly suppresses tube formation, suggesting that β(3)-endonexin is proangiogenic. However, neither treatment with the antiangiogenic mβCTPs nor knockdown of endogenous β(3)-endonexin affects integrin-mediated HUVEC adhesion and migration, indicating that their antiangiogenic effect may not rely on directly regulating integrin activity. Importantly, both treatment with the antiangiogenic mβCTPs and knockdown of endogenous β(3)-endonexin in HUVECs inhibit VEGF expression and cell proliferation, thereby providing mechanistic explanations for the functional consequences. CONCLUSION: Our results suggest that the antiangiogenic mβCTPs can interact with β(3)-endonexin in vascular endothelial cells and suppress its function in regulating VEGF expression and cell proliferation, thus disclosing a unique pathway that may be useful for developing novel antiangiogenic strategies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12964-018-0248-8) contains supplementary material, which is available to authorized users.